Comics studies : a guidebook - Hatfield, Charles, 1965-; Beaty, Bart (New Brunswick, New Jersey : Rutgers University Press, 2020)
"In the twenty-first century, the field of comics studies has exploded. Scholarship on graphic novels, comic books, comic strips, webcomics, manga, and all forms of comic art has grown at a dizzying pace, with new publications, institutions, and courses springing up everywhere. The field crosses disciplinary and cultural borders and brings together myriad traditions. Comics Studies: A Guidebook offers a rich but concise introduction to this multifaceted field, authored by leading experts in multiple disciplines. It opens diverse entryways to comics studies, including history, form, audiences, genre, and cultural, industrial, and economic contexts. An invaluable one-stop resource for veteran and new comics scholars alike, this Guidebook represents the state of the art in contemporary comics scholarship"--
Comic strips / Ian Gordon -- Comic books / Charles Hatfield -- Underground and alternative comics / Roger Sabin -- European traditions / Bart Beaty -- Manga / Frenchy Lunning -- The graphic novel / Isaac Cates -- Comics industries / Matthew P. McAllister and Brian MacAuley -- Readers, audiences, and fans / Benjamin Woo -- Children and comics / Philip Nel.
Includes bibliographical references and index.
Keywords: Comic books, strips, etc. -- History and criticism